Waiting for Godot at The Mandelbaum Gate. Issue 9 (21st October 2018) - Reizbaum, Marilyn
ABSTRACT: Many have pointed to the uncharacteristic form of The Mandelbaum Gate within Spark's oeuvre, including Spark herself. Readers have attributed the formal difference to the weightiness of Spark's topic – the Middle East conflict circa 1960, along with the matching personal schisms; indeed, the subject of Israel-Palestine is often noted for overwhelming any presentation in any form, and any effort to resolve it. This essay proposes the concept of literary Zionism, a trope for modernist non-conclusions and attenuated ideals such as the Zionist project, as a way of accounting for the novel's formal elements. The essay examines in particular the role of the Eichmann trial and the interpolated figure of Samuel Beckett's Godot, arguing that the verdict's impact for Zionism's trajectory is inflected by the deferred outcome of Zionism's legacy, as illustrated by Spark's novel form. The case for literary Zionism may be read either positively in terms of a modernist sensibility of narrative open-endedness or alternatively (or at once) as driven by Lauren Berlant's idea of 'cruel optimism'.